Legal Protection for Workers Experiencing Termination of Employment Due to the Impact of Digitalization - Hamielly Cortez Lim (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Labor in Indonesia is regulated by Labor Law no. 13 of 2003. Problems that arise in the world of work are usually caused by a less harmonious relationship between employers/employers and workers/employees. With this digitization, the company in question is taking efficiency measures, so that the company can take steps to lay off employees. Efficiency here means limiting the use of resources in the processes used by companies within their respective companies. The author uses the method of normative legal documents. In this method, the use of legal norms becomes the subject of study, and law is studied normatively by looking at it from an internal perspective. Protection of workers' rights, namely the implementation of wages that must be paid to the employer at the time of dismissal. The right in the form of compensation is divided into three parts including severance pay, gratuity pay and compensation for other rights obtained by workers/employees.